Review of the Chinese species of Deleaster Erichson, 1839 (Coleoptera, Staphylinidae, Oxytelinae) with a mitogenome of Deleaster bactrianus Semenov, 1900 - Wang, Lin-Fei; Lü, Liang (Zootaxa, 2021)
Deleaster Erichson is an oxyteline genus with only 12 species worldwide, but its members have very distinctive appearance and bear primitive characters, which are particularly critical in understanding the evolution of Oxytelinae. Here we review the species in China and provide a new record species, Deleaster bactrianus Semenov, to Chinese fauna of this genus. Additionally, we describe the first complete mitochondrial genome of Deleaster.